Presuppositions and Common Ground in Utterances Between Characters With Social Class Issues in the Crazy Rich Asians - Firyal Khansa Sabrina; Nur Utami Sari'at Kurniati; Sari Rejeki (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
Crazy Rich Asians is a romantic comedy movie that raises the theme of social class. The issue of social class can be found by observing the context and utterances of the speakers and interlocutors in the movie. This study aims to identify, analyze, and describe the types of presuppositions and common ground in the conversations between the characters in the Crazy Rich Asians movie with of social class issue in it. So that the meaning contained in the speech between the characters in it can be conveyed well. This study uses a qualitative method with a note-taking method as a data collection method. Where data is obtained by observing the utterances between the characters in the movie. The data will then be analyzed using matching techniques, and the results are presented descriptively. The results of the study showed 15 which have been analyzed data contained presuppositions. The data is divided into one existential presupposition, four factual presuppositions, four lexical presuppositions, four structural presuppositions, one non-factual presupposition, and one counterfactual presupposition. In this study, presuppositions analyzed are inseparable from the issue of social class.